INFORMASI LOKASI TEMPAT IBADAH DI KOTA JAMBI BERBASIS ANDROID: ANDROID, LOCATION INFORMATION PLACES OF WORSHIP IN THE CITY OF JAMBI - Nurjani, Yeni (LP2M STMIK Nurdin Hamzah Jambi, 2017)
Public facilities in Jambi Province especially in Jambi City is needed by the public, where one of them is a place of worship. Information about places of worship is considered very necessary, in order to know the location of the place of worship and instructions to get to the place of worship. Making this application in the form of Augmented Reality (AR) to search the location of places of worship in the city of Jambi consisting of mosques, churches, monasteries, and temples with a platform to support the application screen. the database used is SQLite. Stages of this study are the stages of planning, stages of analysis, and stages of application design. The results of this study in the form of applications running on the smartphone operating system android, this application is expected to provide information quickly to find places of worship desired by the user.